TRANSLATION ABILITY, READING HABIT, AND READING SKILL IN VOCATIONAL SCHOOL STUDENTS IN INDONESIA: A CORRELATION - Maximilian, Aksendro (LPPM STKIP PGRI Bandar Lampung, 2020)
The present study aimed to investigate the correlation between 1) translation ability and reading skill; 2) reading habit and reading skill; 3) translation ability, reading habit and reading skill. This study employed a correlational method as its research design. This study was implemented in a vocational school in Kota Bandar Lampung, Indonesia. The sample comprised 30 tenth grade vocational school students of SMK PGRI 2 Bandar Lampung. The data were collected from conducting two tests (reading test and translation test) and reading habit questionnaire. The data analysis was conducted with product moment and multiple linear regressions. The result of the study revealed that: 1) there is a correlation between students’ translation ability and students’ reading skill; 2) there isa correlation between students’ reading habit and students’ reading skill; 3) there is a correlation between students’ translation ability and reading habit toward students’ reading skill. Finally, this paper discusses some findings related to the correlation between translation ability, reading habit and reading skill in the context of Indonesian vocational school students.